Efficacy and safety of polydioxanone thread embedded at specific acupoints for non-specific chronic neck pain: a study protocol for a randomized, subject-assessor-blinded, sham-controlled pilot trial - Kim, Eunseok (Trials, 2018)
BACKGROUND: This study aims to evaluate the efficacy and safety of thread-embedding acupuncture (TEA) with polydioxanone thread embedded at various acupoints, compared with sham TEA, for the treatment of non-specific chronic neck pain. METHODS/DESIGN: This study will be an 8-week-long, two-armed, parallel, randomized, subject-assessor-blinded, sham-controlled pilot trial. Fifty eligible patients will be randomly allocated into the real TEA group or the sham TEA group. The real TEA group will receive TEA treatment at 14 fixed acupoints in the neck region. The sham TEA group will receive the same treatment as the real TEA group, but with a sham device with the thread removed. Both groups will receive treatment once a week for a total of four sessions. The primary outcome will be the mean change in the visual analog scale (VAS) from baseline to week 6 (2 weeks post intervention). Clinical relevance (ratio of the number of patients with decreases on the VAS of ≥15 mm or with percentiles ≥ 30% and ≥ 50% relative to baseline to the total number of patients), Neck Disability Index, pressure pain threshold, the Hospital Anxiety and Depression Scale, EuroQol 5-Dimensions questionnaire, Patient Global Impression of Change, blinding test, and adverse events will be used to assess secondary outcomes. DISCUSSION: The results of this study will provide valuable data for a large-scale clinical trial to evaluate the clinical effects of polydioxanone TEA in the treatment of patients with non-specific chronic neck pain. TRIAL REGISTRATION: Clinical Research Information Service (CRIS), Republic of Korea, KCT0002452. Registered on 6 September 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-3058-9) contains supplementary material, which is available to authorized users.